Cation Exchange in Smectites as a New Approach to Mineral Carbonation - Zeyen, Nina; Wang, Baolin; Wilson, Sasha; Paulo, Carlos; Stubbs, Amanda R.; Power, Ian M.; Steele-Maclnnis, Matthew; Lanzirotti, Antonio; Newville, Matthew; Paterson, David J.; Hamilton, Jessica L.; Jones, Thomas R.; et al. (Frontiers in Climate, 2022)
Mineral carbonation of alkaline mine residues is a carbon dioxide removal (CDR) strategy that can be employed by the mining industry. Here, we describe the mineralogy and reactivity of processed kimberlites and kimberlite ore from Venetia (South Africa) and Gahcho Kué (Canada) diamond mines, which are smectite-rich (2.3–44.1 wt.%). Whereas serpentines, olivines, hydrotalcites and brucite have been traditionally used for mineral carbonation, little is known about the reactivity of smectites to CO2. The smectite from both mines is distributed as a fine-matrix and is saponite, Mm+x/mMg3(AlxSi4-x)O10(OH)2·nH2O, where the layer charge deficiency is balanced by labile, hydrated interlayer cations (Mm+). A positive correlation between cation exchange capacity and saponite content indicates that smectite is the most reactive phase within these ultramafic rocks and that it can be used as a source of labile Mg2+ and Ca2+ for carbonation reactions. Our work shows that smectites provide the fast reactivity of kimberlite to CO2 in the absence of the highly reactive mineral brucite [Mg(OH)2]. It opens up the possibility of using other, previously inaccessible rock types for mineral carbonation including tailings from smectite-rich sediment-hosted metal deposits and oil sands tailings. We present a decision tree for accelerated mineral carbonation at mines based on this revised understanding of mineralogical controls on carbonation potential.